(untitled) (World Science, 2016)
Тhe relationship between the de-concentration of the logistic infrastructure (logistic sprawl) and the extensive development of urbanized areas through fragmentation of urban fabric (urban sprawl) in the context of a globalized economy and post-modern public values is the subject of this article. The factors for the emergence of the so called “brown-fields” are analysed and their potential is assessed considering the possibilities for reintegration of the urban logistics infrastructure into the urban environment. The opportunities, provided by the spatial structure transformation of the post-industrial cities in Central and Eastern Europe, are elaborated. These are supposed to offer sustainable solution for the logistics’ problems within “the last mile”. The objectives that the urban consolidation centre or complex (UCC) is expected to obtain, as well as the site selection criteria are defined. The structures of Budapest, Warsaw and Prague are studied in terms of theoretical possibility to ensure an urban space for the deployment of urban distribution centres (UDC) at an appropriate distance from the urban core and with parameters that do not restrict future development of logistics objects. The presence of a large enough mass of consumers within the 15 minutes’ automotive access is a necessary condition for sustainable functioning of the urban logistics centre. City’s average speed of transport vehicles and the level of congestion, are essential for defining the spatial range of the 15 minutes’ isochrone.